Effect of Desiccation on Ashcrete (HSDA)-treated Soft Soil used as Flexible Pavement Foundation; Zero carbon stabilizer approach - Onyelowe, Kennedy C.; Tome, Sylvain; Usungedo, Thompson; Etim, Roland K.; Onuoha, Ifeanyi C.; Attah, Imoh C. (International Journal of Low-Carbon Technologies, 2022)
The potential of using ashcrete to improve the microstructural, microspectral and shrinkage properties of expansive soils has been investigated under laboratory conditions. In addition to microstructural, three chemical modulus (TCM) and microspectral examinations, responses to linear shrinkage, volumetric shrinkage and crack width were also investigated using 30-day drying periods for expansive soil treated with ash cement. Moisture-related infrastructures such as the sub-floor of resilient pavements are prone to moisture by the rise and fall of the water table during seasonal changes. Therefore, the effect of soil improvement on soil morphology, chemical content and microspectral patterns was investigated. The soil was classified and characterized as (A-7-6) high plasticity soil and poor classification conditions. The hybrid sawdust ash (SDA) known as ashcrete, which has zero carbon footprint was obtained by activating SDA by mixing it with a reformulated activator material (a mixture of 8 M NaOH and a solution of NaSiO2 in a 1:1 ratio). The zero carbon cement was further used in percent-by-weight proportions of 3, 6, 9 and 12 for the soil improvement. X-ray fluorescence (XRF) and scanning electron microscopy (SEM) experiments were carried out to evaluate the pozzolanic resistance via the chemical composition of the oxide, TCM and the profile of the surface contour of the additives and the soil. XRF exposures revealed that the additives had lower pozzolanic resistance, which increased with the improved mixtures thus forming an improved soil mass. In addition, it showed that TCM silica moduli dominated soil stabilization with ashcrete. Scanning electron microscopy examination showed an increase in soil-ettringite and gel formation with the addition of ashcrete. Also, the microspectral studies of chemical oxide EDXRF and XRD have shown excellent results at 12 mass percent cement and soil cement, which has optimized aluminosilicate formation more than 70% and formation of calcite and quartz that has shown the potential of a zero carbon stabilization geomaterial ash cement as a good complementary binder.
Keywords: Zero carbon stabilizer; Desiccation; Soil